Online professional development for librarians in the workplace and the problem of multitasking - Boštjan Batič; Sabina Ograjšek; Katja Košir; Janja Usenik (Vjesnik Bibliotekara Hrvatske, 2025)
Objective. This survey aimed to identify which activities that can lead to multitasking librarians do at the same time as their online professional development at work, and how often they perform them.